2014
DOI: 10.1080/14786419.2014.950960
|View full text |Cite
|
Sign up to set email alerts
|

A new triterpene and protective effect ofPeriploca somaliensisBrowicz fruits against CCl4-induced injury on human hepatoma cell line (Huh7)

Abstract: The potential hepatoprotective effect of the methanolic extract of Periploca somaliensis Browicz fruits, its different fractions (n-hexane, chloroform and n-butanol) and the major isolated compound ursolic acid was evaluated using the human hepatoma cell line (Huh7) based on the changes in the activity of aspartate aminotransferase, alanine transaminase, glutathione and superoxide dismutase. Each sample was tested at three different concentrations (1000, 100 and 10 μg/mL). All tested samples exhibited a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(18 reference statements)
2
8
0
Order By: Relevance
“…Ursolic acid is a pentacyclic triterpene extracted and purified from many plant species that presents considerable pharmacological effects [5]- [11] [16]. In the present study, some of the UA derivative compounds were able to reduce the viability of A549 cells and, among these, the UAD1 showed better results.…”
Section: Effect Of the Ursolic Acid Derivatives On Cell Viability Nfsupporting
confidence: 47%
See 1 more Smart Citation
“…Ursolic acid is a pentacyclic triterpene extracted and purified from many plant species that presents considerable pharmacological effects [5]- [11] [16]. In the present study, some of the UA derivative compounds were able to reduce the viability of A549 cells and, among these, the UAD1 showed better results.…”
Section: Effect Of the Ursolic Acid Derivatives On Cell Viability Nfsupporting
confidence: 47%
“…Despite the advances in the chemotherapy, the results of the lung cancer treatment are not good enough; being necessary the seeking of new therapeutic strategies and the development of new drugs [4]. In this context, the ursolic acid (UA), a triterpene widely distributed in plant species, becomes the target of studies that investigate its antitumor potential [5] [6] [7] [8]. Moreover, structural modifications in the carbons 3, 12 and 28, and the rings A, C and D (Figure 1) are the potential target to increase the antimicrobial, antioxidant, anti-inflammatory or antitumor activities of the ursolic acid [9] [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that differential extracts of Thai perilla nutlets would vary in their chemical composition and therefore also in their potency of biological activities. This study chemically characterizes different extracts of Thai perilla nutlets and investigates both their antioxidant activity using a suite of assays including the 2,2′‐azinobis‐(3‐ethylbenzothiazoline‐6‐sulphonic acid) diammonium salt (ABTS) and 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) radical scavenging assays, the 2,2′‐azo‐bis(2‐amidinopropane) dihydrochloride (AAPH)‐induced hemolysis assay; a cell‐based model in the study of free‐radical‐induced disruption of cell membranes (Pervin et al, ; Sekiya et al, ), and their protective effects against iron‐induced oxidative stress in human hepatocellular carcinoma (HuH7) cells; an established model to investigate the hepatoprotective effects of plant extracts (Abdel‐Monem, Kandil, Abdel‐Naim, & Abdel‐Sattar, ; Torres‐Gonzalez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In 1971, oleanolic acid ( 172 ), together with maslinic acid ( 175 ), was first isolated from the genus Periploca [70]. Two known triterpenes ( 177 , 178 ) [10,87] characterized by a 13,28-lactone ring were discovered from P. laevigata and P. somaliensis , respectively. Additionally, three new triterpenoid acids of the oleanane series, named P1, P2, P3 ( 183 – 185 ), were isolated from the twigs of P. calophylla , without definite chemical structures [89].…”
Section: Chemical Constituents From the Genus Periplocamentioning
confidence: 99%
“…Its mechanism of promoting wound healing was intensely associated with the activation of the Src/ERK and PI3K/Akt pathways mediated by Na/K-ATPase [200]. Moreover, Abdel-Monem and co-workers [10] reported that ursolic acid played an important role in the protective effect against CCl 4 -induced injury on human hepatoma cell line (Huh7). Additionally, the antiacetylcholinesterase activities of triterpenes 199 and 198 with esterification of the alcohol function at C-3 were lower than that of lupeol ( 197 ).…”
Section: Biological Activitiesmentioning
confidence: 99%